Optimal network restructure via improved whale optimization approach - Abd Elazim, Sahar M.; Ali, Ehab S. (International journal of communication systems, 2021)
Summary Latterly, reduction of power loss in distribution system is the objective of many researches due to its impact on total costs and voltage profiles. It can be handled by optimal restructure of radial distribution system (RDS). This article introduces an innovative approach to restructure of RDS by electing the optimal switches combination subject to the system operating constraints, which is improved whale optimization approach (IWOA). The suggested approach combines exploitation of WOA with exploration of differential evolution (DE), and thus, it supplies a promising candidate solution. The suggested approach is tested on IEEE 33 and 69 bus RDS. The superiority of the suggested approach compared with other well‐known approaches is verified through simulation results by observation of total losses, cost, and saving. Also, the impact of alterable loading is investigated to prove the effectiveness of the suggested IWOA. The improvement of voltage profiles is shown in Figure 1 due to the suggested restructure. Also, the ohmic loss with the suggested restructure based on IWOA is reduced by 56.17% compared with the original one. Thus, it provides a promising performance over other approaches reported in literature. Consequently, the cost is smaller, and net saving is greater than others.